1991
DOI: 10.1002/ar.1092290213
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical demonstration of amelogenin penetration toward the dental pulp in the early stages of ameloblast development in rat molar tooth germs

Abstract: In order to examine the synthesis and secretion of enamel protein by ameloblasts in their early stages of development, immunohistochemical localization was carried out at light and electron microscopic levels using a monoclonal antibody produced in a preliminary experiment. Materials used were tooth germs of mandibular first molars of rats at 0-5 days after birth. Immunoblot analysis after two-dimensional electrophoresis revealed that antigen molecules recognized by the monoclonal antibody were amelogenins of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
1
2

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 38 publications
9
56
1
2
Order By: Relevance
“…Snead et al (1984) isolated RNA from first molars of mice of various ages and found greatest hybridization to a radiolabeled amelogenin probe at birth and in 1 day postnatal mice. Results from immunohistochemistry experiments using anti-amelogenin antibodies have suggested that expression begins in pre-ameloblasts in rat molars (Inai et al, 1991;Bronckers et al, 1993). We, however, have not found evidence for expression in any part of the tooth that does not have some mineralized matrix present.…”
Section: Transgenic Mice Specifically Express Pgalactosidase Activitycontrasting
confidence: 74%
“…Snead et al (1984) isolated RNA from first molars of mice of various ages and found greatest hybridization to a radiolabeled amelogenin probe at birth and in 1 day postnatal mice. Results from immunohistochemistry experiments using anti-amelogenin antibodies have suggested that expression begins in pre-ameloblasts in rat molars (Inai et al, 1991;Bronckers et al, 1993). We, however, have not found evidence for expression in any part of the tooth that does not have some mineralized matrix present.…”
Section: Transgenic Mice Specifically Express Pgalactosidase Activitycontrasting
confidence: 74%
“…Laminin epitopes are lost as pre-ameloblasts initiate amelogenin secretion (Inai et al, 1991) and do not appear again until ameloblasts transition to the maturation stage (Nanci et al, 1993). In place of the basement membrane under secretory-stage ameloblasts is a mineralization front apparatus that initiates and elongates thin ribbons of amorphous calcium phosphate (Beniash et al, 2009;JP Simmer et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Several laboratories showed that the amelogenin was detected in the cytoplasm lysosome and stippled material-like substance adjacent to the coated pits of plasma membrane in presecretory ameloblasts and odontoblasts, suggesting that it is likely that amelogenin might be taken up by an endocytic pathway (32)(33)(34). Recently, some integral membrane proteins binding amelogenin have been identified by using the yeast twohybrid assay (35).…”
Section: Discussionmentioning
confidence: 99%